Evaluasi Efektivitas Website Sekolah SMK Wiyata Satya Dengan Metode Pieces - Irma Suryani; Nur Nawaningtyas Pusparini (Pusat Riset dan Inovasi Nasional, 2024)
An educational institution is required to keep up with technological advancements, especially in the field of information technology. The official website of SMK Wiyata Satya, https://www.wiyatasatya.sch.id, established on April 8, 2015, plays a crucial role in promoting and introducing the school to the community. The use of this website aims to reach a broader audience. Despite its advantages in accessibility and speed of information delivery, there are still some issues, such as the lack of an online registration feature, reliance on contact persons via WhatsApp, and incomplete information. The author employs the PIECES framework to evaluate the quality of the information system service and measure customer satisfaction. The PIECES method consists of six parameters: performance, information, economy, control, efficiency, and service. This method is chosen for its ability to provide a detailed and comprehensive evaluation. The evaluation results indicate user satisfaction with the use of the website as a promotional tool and a source of information. The average satisfaction level reflects the majority's contentment with the platform.